Religious festivals and stock market returns: Evidence from south Asian countries - Mahmud, Aslam; Rahman, Md. Habibur; Rana, Shohel (Asian Economic and Financial Review, 2025)
This study examines the impact of major religious festivals on stock market returns across five countries in South Asia - Bangladesh, India, Nepal, Pakistan, and Sri Lanka - to assess how cultural factors influence stock market behavior. Religious traditions are deeply embedded in South Asian societies and significantly shape economic behavior and investor sentiment, creating potential market anomalies during culturally significant periods. Utilizing a comprehensive dataset and exploring Ordinary Least Squares (OLS), GARCH (1,1), and GJR-GARCH (1,1) methods, the seasonality of returns during key religious periods in South Asia has been analyzed. The results reveal significant favorable abnormal returns during the last ten days of Ramadan in Bangladesh and, to a lesser degree, in Pakistan. In contrast, other markets exhibit minimal or insignificant effects during major festivals, such as Diwali, Vesak, and Dashain, suggesting heterogeneous cultural influences on financial market behavior within the region. Our findings suggest that while anomalies related to religious festivals are diminishing, they remain potent in certain markets, particularly in Bangladesh. This research contributes to the literature in the field of behavioral finance by offering a novel, multi-country analysis using long-memory data from largely under-researched emerging markets. The results offer practical implications for investors, regulators, and policymakers in understanding market dynamics driven by religious culture.